Endoscopic ultrasound‐guided fine needle aspiration versus biopsy for diagnosis of autoimmune pancreatitis: Systematic review and comparative meta‐analysis. Issue 7 (17th November 2020) - Yoon, Seung Bae; Moon, Sung‐Hoon; Song, Tae Jun; Kim, Jong Hyeok; Kim, Myung‐Hwan
Abstract : Background: Endoscopic ultrasound (EUS) is recommended for guiding the acquisition of pancreatic tissue in patients with suspected autoimmune pancreatitis (AIP). Data comparing EUS‐guided fine needle aspiration (FNA) and fine needle biopsy (FNB) sampling in the diagnosis of AIP are limited. Methods: A comprehensive literature search of the PubMed, EMBASE, and Ovid MEDLINE databases was conducted until April 2020. The pooled rates of diagnostic yield for the histologic criteria of AIP, histologic tissue procurement, and adverse events were compared between FNA and FNB. Diagnostic yields were also compared between 19 gauge (G) and 22G needles. Results: This meta‐analysis included nine studies comprising 309 patients with AIP who underwent FNA and seven studies comprising 131 patients who underwent FNB. The pooled diagnostic yields for level 1 or 2 histology criteria of AIP were 55.8% (95% confidence interval (CI) 37.0–73.9%, I 2  = 91.1) for FNA and 87.2% (95% CI 68.8–98.1%, I 2  = 69.4) for FNB ( P  = 0.030). The pooled histologic procurement rates for FNA and FNB were 91.3% (95% CI, 84.9–97.6%, I 2  = 82.9) and 87.0% (95% CI, 77.8–96.1%, I 2  = 40.0), respectively ( P  = 0.501). Adverse events were comparable between two groups. When analyzed by needle size, the diagnostic yield was better with a 19G needle than with a 22G needle (88.9% vs. 60.6%, P  = 0.023). Conclusions: The diagnostic yield may be better with FNB needles than with FNA needles for the diagnosis of AIP, despite the similar rate of histologic tissue procurement. A quantitative definition for the histologic sample adequacy for AIP may be warranted.